Introduction of SARS‐CoV‐2 C.37 (WHO VOI lambda) in the Sao Paulo State, Southeast Brazil. Issue 3 (20th October 2021) - Kashima, Simone; Slavov, Svetoslav N.; Giovanetti, Marta; Rodrigues, Evandra S.; Patané, José S. L.; Viala, Vincent L.; Santos, Elaine V.; Evaristo, Mariane; de Lima, Loyze P. O.; Martins, Antonio J.; dos Santos Barros, Claudia R.; Marqueze, Elaine C.; et al.
Abstract: The Lambda variants of interest (VOI) (C37/GR/452Q.V1/21G) was initially reported in Lima, Peru but has gained rapid dissemination through other Latin American countries. Nevertheless, the dissemination and molecular epidemiology of the Lambda VOI in Brazil is unknown apart from a single case report. In this respect, we characterized the circulation of the SARS‐CoV‐2 Lambda VOI (C37/GR/452Q.V1/21G) in Sao Paulo State, Brazil. From March to June 2021, we identified seven Lambda isolates in a set of approximately 8000 newly sequenced genomes of the Network for Pandemic Alert of Emerging SARS‐CoV‐2 variants from Sao Paulo State. Interestingly, in three of the positive patients, the Lambda VOI infection was probably related to a contact transmission. These individuals were fully vaccinated to COVID‐19 and presented mild symptoms. The remaining positive for Lambda VOI individuals showed different levels of COVID‐19 symptoms and one of them needed hospitalization (score 5, WHO). In our study, we present a low level of Lambda VOI circulation in the Sao Paulo State. This reinforces the essential role of molecular surveillance for the effective SARS‐CoV‐2 pandemic response, especially in regard to circulating variants. Highlights: Our study shows the low circulation of the Lambda variants of interest (VOI) in the São Paulo State. Two distinct Lambda VOI introductions may have occurred in the Sao Paulo State. Epidemiological data revealed Lambda VOI transmission in three cases of fully vaccinated individuals.